2018
DOI: 10.1002/14651858.cd011940.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Adverse side effects of dexamethasone in surgical patients

Abstract: A single dose of dexamethasone probably does not increase the risk for postoperative infection. It is uncertain whether dexamethasone has an effect on delayed wound healing in the general surgical population owing to imprecision in trial results. Participants with increased risk for delayed wound healing (e.g. participants with diabetes, those taking immunosuppressive drugs) were not included in the randomized studies reporting on delayed wound healing included in this meta-analysis; therefore our findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 97 publications
7
78
1
3
Order By: Relevance
“…Therefore, we stratified our randomization per centre. Consistent with the literature, we observed higher BG concentrations in the patients treated with corticosteroids . None the less, the efficacy of liraglutide was comparable, whether patients received intraoperative corticosteroids or not.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we stratified our randomization per centre. Consistent with the literature, we observed higher BG concentrations in the patients treated with corticosteroids . None the less, the efficacy of liraglutide was comparable, whether patients received intraoperative corticosteroids or not.…”
Section: Discussionsupporting
confidence: 91%
“…However, there was only infrequent reporting of wound infections and wound healing complications in the studies included in our review. Recently, Polderman et al concluded that a single dose of dexamethasone does not affect the risk of infections, whereas no definite conclusion was possible for delayed wound healing. In conclusion, our analysis provides solid evidence for the notion that i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dexamethasone for PONV is well‐established, but its use remains debated in the medical literature due to potential for side effects including poor wound healing and hyperglycemia. A recent meta‐analysis of dexamethasone in surgical patients found no increase in the risk of postoperative infection (OR 1.01, 95% CI 0.80‐1.27), but were unable to examine the effect on wound healing due to the imprecision in the available randomized trials . Dexamethasone was found to have a mild increased in glucose in patients without diabetes for the first 12 hours after surgery (mean difference 13 mg/dL, 95% CI 6‐21).…”
Section: Discussionmentioning
confidence: 99%